ARTIFICIAL INTELLIGENCE-DRIVEN TESTING IN EFL/ESP CLASSROOMS - Olena Zhyhadlo; Inna Zaiarna (Інформаційні технології і засоби навчання)
This article explores the application of Artificial Intelligence (AI)-driven tools, particularly ChatGPT, for creating vocabulary test tasks in EFL/ESP classrooms. The research aims to evaluate the quality of vocabulary test tasks generated by ChatGPT by applying established criteria, including relevance, reliability, interactiveness, practicality, and impact. It investigates how ChatGPT-generated tasks meet these criteria and provides practical recommendations for educators to optimize the quality of AI-generated assessments. The authors indicate that criteria such as relevance, practicality, interactivity, and impact can be fully satisfied in ChatGPT-generated tests. However, the research identifies challenges with the reliability of AI-generated test tasks, primarily due to ambiguities in response choices.